Is humankind approaching its own extinction? - D. Barquero , Marco (2025)
The impacts of humankind on the planet's ecosystems are so noticeable and alarming that the possibility of a mass extinction event and a potential ecological collapse has been raised. However, there is no widespread perception that such processes are occurring or that humanity could become extinct.  This paper presents an analysis of the current state of biodiversity and the factors that have led to the disappearance of a large number of species, as well as the relationship between human actions and their impacts on ecosystems. Finally, it reflects on the possibility that humanity is approaching its own extinction and proposes some actions and alternatives to avoid a potential ecological collapse.